2012
DOI: 10.1074/jbc.m111.327767
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Regulates Yes-associated Protein (YAP) Gene Expression in Colorectal Carcinoma Cells

Abstract: Background: It is unclear how YAP gene expression is controlled in colorectal cancer (CRC) cells. Results: ␤-Catenin/TCF4 complexes directly regulate YAP gene expression through a novel DNA enhancer element. Conclusion: YAP is a direct Wnt/␤-catenin target gene, and its expression is required for CRC cell growth. Significance: Aberrant Wnt/␤-catenin signaling may account for oncogenic YAP expression in intestinal cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
236
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(246 citation statements)
references
References 43 publications
7
236
1
2
Order By: Relevance
“…miR-135b has also been reported to induce Wnt signalling pathway by the suppression of APC in colorectal cancers 16 , and the Hippo pathway has been reported to inhibit the Wnt pathway during heart development 49 . This crosstalk has also been described in cancer cells when the Hippo pathway retains b-catenin in the cytoplasm through a physical interaction between phosphorylated TAZ/YAP and b-catenin 50,51 . Our results suggest that the upregulation of miR-135b in lung cancer may antagonize the Hippo pathway and inhibit the Wnt/b-catenin pathway through direct APC and b-TrCP suppression.…”
Section: Discussionmentioning
confidence: 73%
“…miR-135b has also been reported to induce Wnt signalling pathway by the suppression of APC in colorectal cancers 16 , and the Hippo pathway has been reported to inhibit the Wnt pathway during heart development 49 . This crosstalk has also been described in cancer cells when the Hippo pathway retains b-catenin in the cytoplasm through a physical interaction between phosphorylated TAZ/YAP and b-catenin 50,51 . Our results suggest that the upregulation of miR-135b in lung cancer may antagonize the Hippo pathway and inhibit the Wnt/b-catenin pathway through direct APC and b-TrCP suppression.…”
Section: Discussionmentioning
confidence: 73%
“…Our results showed that Tau could induce apoptosis in CRC cells and inhibit their proliferation, and the mechanism underlying these effects involves increasing the level of MST1 in CRC cells, which then upregulates the expression of pro-apoptotic proteins, such as BAX, but downregulates the expression of anti-apoptotic proteins, such as BCL-2. Recent studies have found that the expression levels of MST1 and YAP1 in human colon cancer tissue are significantly higher than those in the adjacent tissues [23,24]. In human primary colon cancer, adenomatous colonic polyposis, or mouse multiple intestinal tumor, the expression of YAP is upregulated, which could also promote the growth of transplanted tumors in a mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of TAZ showed an exceptionally strong association with poor patient survival from non-small lung cancer and thyroid carcinoma (25,26). Alterations in this gene and/or its molecular partners YAP and TEAD have also been reported in cancers derived from colon, lung, liver, or esophagus (27)(28)(29). A very recent study by Camargo and his group has shown that the tumor suppressor LKB1, which is known for its ability to regulate cellular metabolism through AMPK activation, also regulates Hippo signaling (30).…”
Section: Introductionmentioning
confidence: 99%